Observaciones sobre parámetros anatómicos de los ovarios del coipo (Myocastor coypus bonariensis) en la madurez sexual - Felipe A.E. (2015)
The aim of the present study was to determine anatomical parameters of ovaries of coypu in the sexual maturity throughout in situ and post extraction analysis. Thirty two virgin and sexually mature females aged between 6 and 9 months (mean 7 ± 0.84 months) and weighted 4.795 ± 399.6 gr were used. Ovaries were degreased and weighed after their in situ identification with the anatomical relations. The shape and the superficial aspect were registered and their cephalocaudal, dorsoventral and lateromedial diameters were recorded. Ovaries volume were determined considering their diameters. Ovaries were located in the sublumbar area, showed ovoidal shape and creamy white colour. The ovarian surface was lobed or with convolutions and protrusions. The average weight of the ovaries was 0.12 ± 0.04 g and the average volume was 561.99 ± 144.32 mm3. No statistical differences were detected between the right and left ovary of the same animal. The ovaries were supported by the distal mesovarium. Each ovary was partially surrounded by the oviductal fimbriae and by an open or incomplete ovarian bursa which was limited by the distal mesovarium and the mesosalpinx. The ovarian bursa closed the cefhalic half of each ovary, showing a large communication with the peritoneal cavity.